Fluid systems and fracture development during syn-depositional fold growth: An example from the Pico del Aguila anticline, Sierras Exteriores, southern Pyrenees, Spain. (January 2015) - Beaudoin, Nicolas; Huyghe, Damien; Bellahsen, Nicolas; Lacombe, Olivier; Emmanuel, Laurent; Mouthereau, Frédéric; Ouanhnon, Laure
Abstract: This paper reports an integrated, spatio-temporal analysis of the fracture-controlled paleo-fluid system in the Pico del Aguila anticline, a N–S trending fold located in the Sierras Exteriores, the southern front of the Spanish Pyrenees. Eight fracture sets (joints or faults) are recognized throughout the fold and are separated into a fracture sequence that is defined using field relationships and the remarkable temporal constraints offered by the syn-tectonic sedimentary deposits. This fracture sequence records a complex Paleocene to Early Oligocene structural evolution, including map-view, clockwise rotation and tilting of the fold axis. The geochemical analysis of calcite cements from the different mineralized fracture/vein sets reveals a compartmentalized fluid system during most of fold development. This initial paleofluid system was later perturbed when bending-related fractures associated with foreland flexure and outer arc extension triggered small-scale, vertical fluid migration. Fractures developed in shallow strata facilitated downward migration of surficial fluids that controlled the paleo-fluid system in the Late Priabonian/Stampian continental deposits. The study of the Pico del Aguila anticline depicts for the first time the evolution of a fluid system in a shallow, syn-depositional compressional setting, and results further strengthen the statement that fluids migrate vertically across stratigraphic boundaries take place during fold hinge-related deformation. Graphical abstract: Highlights: Fluid system deciphered during syn-sedimentary folding. Role of tectonic and sedimentary environment on fluid system evolution. Role of burial on vertical permeability of fractures. Fracture development witnesses fold rotation around a vertical axis.